2017
DOI: 10.5455/msm.2017.29.14-16
|View full text |Cite
|
Sign up to set email alerts
|

T-lymphocyte Subsets as a Prognostic Factor in a Clinical Course of Chickenpox

Abstract: Objective:To investigate possible prognostic values of CD4+, CD8+ T-lymphocytes, CD4/CD8 ratio to clinical course of chickenpox in immunocompetent hosts.Materials and methods:We performed a prospective study which included 69 immunocompetent patients with chickenpox who were addmited to Clinic for infectious disease, Clinical Center University of Sarajevo, in a 18 month period. All patients were divided into two groups depending on clinical presentation on admission. Patients with mild clinical form were dedic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…T lymphocyte subsets play an important role in the body's antiviral cellular immunity. 23 24 The results of this study showed that compared with the control group, patients in the observation group had significantly higher serum CD 3 + , CD 4 + , CD 8 + and CD 4 + /CD 8 + levels after treatment. It showed that chlorquinaldol-promestriene vaginal tablets can improve the T lymphocyte levels and cellular immune function of the patient.…”
Section: Discussionmentioning
confidence: 63%
“…T lymphocyte subsets play an important role in the body's antiviral cellular immunity. 23 24 The results of this study showed that compared with the control group, patients in the observation group had significantly higher serum CD 3 + , CD 4 + , CD 8 + and CD 4 + /CD 8 + levels after treatment. It showed that chlorquinaldol-promestriene vaginal tablets can improve the T lymphocyte levels and cellular immune function of the patient.…”
Section: Discussionmentioning
confidence: 63%